Efektivitas Penilaian Diri dan Seja Wat pada Keterampilan Passing Bawah Bola Voli Mata Pelajaran PJOK di SD Kebumen - Mudayat Mudayat; Rendy Wahyudi (Jurnal Syntax Admiration, 2024)
During the COVID-19 pandemic, learning is being conducted deeply. Problems arise when teachers in the field of physical education have difficulty in assessing the skills of their students. Therefore, the purpose of this study was to test the effectiveness of self-assessment and peer assessment of bottom passing skills in volleyball in PJOK subjects at SD Kebumen. The method used is a quantitative approach. Data collection is carried out through a list of questions and techniques using the media. The results showed that there was no significant difference between the assessments carried out by students and teachers. The distribution of data in this study was normal with a significance value of 0.05, and the t-test value for the sample itself was 0.466, while for the pair sample was 0.919, which showed no significant difference. Thus, it can be concluded that this study successfully tested the effectiveness of self-assessment and peer assessment of bottom passing skills in volleyball in PJOK subjects at SD Kebumen.